Interleukin 6 and complement serum level study in Parkinson's disease - Veselý, Branislav; Dufek, Michal; Thon, Vojtech; Brozman, Miroslav; Királová, Silvia; Halászová, Tatiana; Koriťáková, Eva; Rektor, Ivan (Journal of neural transmission, 2018)
The objective of this study is to assess whether elevation of serum inflammatory markers levels may indicate the progression of clinical impairment in Parkinson's disease (PD) patients. In 47 PD patients, the serum levels of the C3 and C4 part of the complement and Interleukin-6 (IL-6) were measured. The results at baseline and after 2 years were correlated with scales measuring memory, depression, motor symptoms, and quality of life. Patients with higher levels of C3 and C4 at baseline had decreased quality of life, verbal ability, and memory. Patients with higher IL-6 at baseline showed worse depression scores at 2 years. Patients with persistently higher levels of C3 and C4 at 2 years had worse quality of life and memory ability. Uncorrected p values are reported due to the exploratory nature of the study. The results indicate an impact of inflammation on non-motor signs and quality of life in PD. The increase of levels of serum inflammatory biomarkers may indicate the progression of non-motor impairment in PD.
Keywords: komplement C3; Male; biologické markery; longitudinální studie; Biomarkers; Interleukin-6; Aged; mužské pohlaví; senioři; Complement C3; komplement 4; lidé; ženské pohlaví; Humans; interleukin-6; Longitudinal Studies; Female; Parkinson Disease; Parkinsonova nemoc; lidé středního věku; Complement C4; Middle Aged